2007
DOI: 10.1111/j.1365-294x.2007.03301.x
|View full text |Cite
|
Sign up to set email alerts
|

Host–parasite kinship in a female‐philopatric bird population: evidence from relatedness trend analysis

Abstract: Conspecific brood parasitism (CBP), an alternative reproductive tactic where some females lay eggs in the nests of other females of the same species, occurs in many animals with egg care. It is particularly common in waterfowl, for reasons that are debated. Many waterfowl females nest near their birthplace, making it likely that some local females are relatives. We analyse brood parasitism in a Hudson Bay population of common eiders, testing predictions from two alternative hypotheses on the role of relatednes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 92 publications
(222 reference statements)
3
59
0
Order By: Relevance
“…1; Laurila and Hario 1988; see also Lehikoinen et al 2006). Thus, the overall nesting conditions also contributed to the varying availability of samples (and varying rate of parasitism; see Andersson and Waldeck 2007;Waldeck et al 2008).…”
Section: Parametermentioning
confidence: 94%
See 4 more Smart Citations
“…1; Laurila and Hario 1988; see also Lehikoinen et al 2006). Thus, the overall nesting conditions also contributed to the varying availability of samples (and varying rate of parasitism; see Andersson and Waldeck 2007;Waldeck et al 2008).…”
Section: Parametermentioning
confidence: 94%
“…Based on this finding, Andersson and Waldeck (2007) and Waldeck et al (2008) concluded that the high host-parasite relatedness among laying Eider hens is not an effect of natal philopatry alone but also forms some additional kin-biasing mechanism. This means that Eider females recognize first-order relatives (siblings, mother-daughter pairs), and possibly also maternal halfsiblings, when laying parasitically in their nests.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations